Pengaruh Kemudahan Informasi Dan Social Media Marketing Terhadap Keputusan Pembelian Online Di Lazada Dengan Kepuasan Pelanggan Sebagai Pemoderasi - Yanis, Fauziah; Kamaruddin, Muhammad Junaid; Sanusi, Yasril Fadlitama (PRoMEDIA, 2023)
This study aims to test and analyze the influence of ease of information and social media marketing on purchasing decisions and put customer satisfaction as moderation. The sample in this study was 152 respondents, who were people and students at various universities. The scope of the number of respondents is based on the approach used by Hair. Data collection techniques use simple random sampling by spreading research questionnaires in the form of google from then spread to social media. The data processing method in this study used Smart PLS (Partial Least Square) software which was used to test hypotheses. The results showed that the ease of information has proven to have a positive and significant effect on purchasing decisions, customer satisfaction has proven to have a positive and significant effect on purchasing decisions social media marketing has proven to have a positive and significant influence on purchasing decisions, customer satisfaction has proven to have a significant effect and can moderate the influence of ease of information on purchasing decisions, and customer satisfaction has proven to have a significant effect and can moderate the influence of social media marketing on purchasing decisions. recommend to the public and students if you want to increase customer satisfaction, it is recommended to be able to further improve social media marketing and ease of information, Because some respondents to this study stated that in increasing purchasing decisions, people and students must be able to maintain the ease of information and social media marketing properly in order to improve purchasing decisions. Students are also expected to maintain the ease of good information, so that the public and students can improve purchasing decisionsKeywords:  Ease of Information, Social Media Marketing, Purchasing Decisions, Customer Satisfaction